William D. Hassett papers - Hassett, William D., 1880-1965.
Correspondence, 3 volumes of diaries (1942-1945), memoranda, and notes pertaining primarily to Hassett's service as secretary to Franklin D. Roosevelt. Includes a chronicle of Roosevelt's wartime activities and a description of the president immediately before his death in Warm Springs, Ga. Correspondents include James Aloysius Farley, Louis Arthur Johnson, Frances Perkins, Franklin D. Roosevelt, and Harry Hines Woodring.
Microfilm edition of diaries available
Microfilm produced from originals in the Manuscript Division.
Journalist and secretary to Franklin Delano Roosevelt.
Collection material in English.
Keywords: Farley, James A. -- 1888-1976 -- Correspondence; Johnson, Louis Arthur, -- 1891-1966 -- Correspondence; Perkins, Frances, -- 1880-1965 -- Correspondence; Roosevelt, Franklin D. -- 1882-1945.; Roosevelt, Franklin D. -- 1882-1945 -- Correspondence; Woodring, Harry Hines, -- 1887-1967 -- Correspondence; World War, 1939-1945.; Journalists; Secretaries, Presidential